2013
DOI: 10.1088/0031-9155/58/16/5693
|View full text |Cite
|
Sign up to set email alerts
|

RBE of kV CBCT radiation determined by Monte Carlo DNA damage simulations

Abstract: Due to the higher LET of kilovoltage (kV) radiation, there is potential for an increase in relative biological effectiveness (RBE) of absorbed doses of radiation from kV cone beam computed tomography (CBCT) sources in reference to megavoltage or Co-60 doses. This work develops a method for accurately coupling a Monte Carlo (MC) radiation transport code (PENELOPE) with the damage simulation (MCDS) to predict relative numbers of DNA double strand breaks (DSBs). The MCDS accounts for slowing down of electrons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 16 publications
5
44
0
Order By: Relevance
“…These differences in photon spectra are in conceptual agreement with other published data [10][11][12][13]23]. For shallow depths, the photon spectrum peak is lower in the out-of-field regions, but for deeper depths, the peak energy is independent of location in or out of the primary beam.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These differences in photon spectra are in conceptual agreement with other published data [10][11][12][13]23]. For shallow depths, the photon spectrum peak is lower in the out-of-field regions, but for deeper depths, the peak energy is independent of location in or out of the primary beam.…”
Section: Discussionsupporting
confidence: 92%
“…For example, studies have shown changes in RBE (or quality factor) of up to 40 % depending on the photon energy spectrum, location in or out of the field [9,[11][12][13]30]. Additionally, Hsiao and Stewart [7] reported changes in RBE and deoxyribonucleic acid (DNA) double-strand breaks (DSB) for various diagnostic X-ray sources and gamma-emitting isotopes, which compared well to measured values.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The Monte Carlo methods form a broad class of stochastic algorithms that proved successful in a variety of disciplines including genetics [14], space physics [15] and economics [16]. While problems might be solvable using deterministic methods, Monte Carlo methods utilize repetition of random sampling to arrive at a numerical result.…”
Section: Characterization Of Radiation Generated By Linacmentioning
confidence: 99%